DOORMATICS (DOORMAT AUTOMATIC SYSTEM) INOVASI KESET BERBASIS PENYEDOT DEBU OTOMATIS SEBAGAI ALTERNATIF PENJAGA KEBERSIHAN LANTAI RUANGAN - Firmansah, Ahmad Febri; Rafiandi, Rizky Nafiar; Andriawan, Fery (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2014)
Human needs a healthy environment to create a comfort life. One aspect of the healthy environment is the cleanness of floor. This project is a automatic doormat used to help people keep the floor always clean. With this automatic doormat, people can keep the floor always clean more effecively rather than using the cleaning service. Keywords : Automatic doormat, Floor cleanness, Healthy environment